Changes in Flavor Compounds during the Production of Xingning Dancong Tea - LI Xiumei, WU Kegang, WEN Rourou, CHAI Xianghua, DUAN Xuejuan, YU Hongpeng, LIU Xiaoli, TAO Zhihua, WANG Pingping, LIN Yahui, DAI Yongping (Shipin Kexue)
The contents of taste and flavor compounds of Xingning Dancong tea at different processing stages were determined by headspace solid-phase microextraction combined with gas chromatography-mass spectrometry (HS-SPME-GC-MS), high performance liquid chromatography (HPLC), and spectrophotometry to explore the effect of each processing stage on tea quality. The results showed that during the production process of Xingning Dancong tea, the contents of taste substances such as water extracts, tea polyphenols, catechin compounds, proteins, free amino acids, theanine, caffeine, and soluble sugars showed a decreasing trend. The astringency and bitterness of tea were reduced, while the fresh and brisk taste was enhanced. In terms of volatile components, the relative contents of alcohols, alkenes, and esters decreased, while the relative contents of alkanes, ketones, aldehydes, and heterocyclic substances increased. Terpene and β-pinene, contributing to a grassy flavor, gradually dissipated, while the relative contents of compounds contributing to floral and fruity aromas such as dihydroactinidiolide, linalool oxide II, linalool oxide IV, benzaldehyde, and phytone increased significantly. The changes in tea flavor substances occurred mainly during the shaking, fermentation, high-temperature fixation and baking stages, ultimately forming Xingning Dancong tea with a rich floral and fruity flavor and a strong and mellow taste.